The effect of moist and dry extrusion processing on growth performance and nitrogen digestibility in the early-weaned pig - Friesen, K.G.; Kats, L.J.; Nelssen, Jim L.; Goodband, Robert D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred pigs (initially 13.0 lb and 21 d of age) were used to assess the differences between moist and dry extruded soybean meal in diets for early-weaned pigs. Dietary treatments included: 1) corn+ dried skim milk+dried whey+casein, 2) corn+soybean meal, 3) corn+dry extruded soybean meal, and 4) com+moist extruded soybean meal. The diets were formulated to contain 1.4% lysine and 24.4% lactose. Soybean meal (with or without extrusion processing) replaced milk protein on an equal lysine basis. Experimental diets were fed for the entire 28 d experiment. On d 14, fecal samples were collected to determine apparent DM and N digestibilities by feeding chromic oxide as an undigestible marker. Average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (FIG) were improved (P< .05) in pigs fed the predominately milk diet from d 0 to 14 postweaning compared to pigs fed soybean meal with or without extrusion processing. For the entire trial (d 0 to 28), ADG was increased in pigs fed the milk based diet compared to pigs fed a soybean meal-based diet. Pigs fed moist extruded soybean meal had a similar ADG to pigs fed the milk diet and had an increased ADG compared to pigs fed dry extruded soybean meal. Average daily feed intake (d 0 to 28) was increased in pigs fed soybean meal (with or without moist extrusion) compared to pigs fed the milk based diet. Pigs fed the milk based diet had improved feed efficiency compared to pigs fed soybean meal with or without extrusion processing. Dry matter and N digestibilities were similar between dietary treatments. These data suggest that extrusion processing can be used to improve soybean meal quality for use in starter pig diets. Moist extrusion produces a superior product compared to dry extrusion for starter pig diets as indicated by increased ADG and improved feed efficiency.
Keywords: Swine; Starter pigs; Extrusion; Soybean meal